STRATEGY OF EMERGENCY RESPONSE OF FLOOD AND LANDSLIDE DISASTER IN PACITAN REGENCY - Faturahman, Burhanudin Mukhamad (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
Disaster emergency response is a series of actions taken when a disaster occurs so that a responsive, precise and accurate action can minimize losses caused by a disaster. The purpose of this study is to describe the phenomena of floods and landslides as well as disaster relief efforts in Pacitan Regency in 2017. The research was carried out through a qualitative descriptive approach. Methods of data collection interviews, observation and documentation. The data analysis phase includes data condensation, data presentation and the final stage, namely drawing conclusions. The results showed that the emergency response strategies for floods and landslides in Pacitan Regency were led by the commander of Dandim 0801 Pacitan as the representative of the regional government. The community response to the disaster was shown by opening a voluntary emergency post. In this emergency disaster process, there are obstacles, namely the disaster relief tool is still traditional. Therefore, with the emergence of a disaster emergency process and the obstacles encountered, it is expected that there will be a strengthening of coordination between government, private and community actors who are oriented towards pre-disaster activities to reduce the risk of disasters.